Safety Culture in Indonesia’s Road Transport - Sri Handayani Handayani; Tri Mulyani Setyowati; Muhammad Iqbal Firdaus (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
Transportation with all of its branches is dependent on an infrastructure which consider safety. Road transport has a large number of accidents, but do not received the same attention on media compare to major accidents in other branch of transportation regarded as dramatic ones. The main objective of this study is to describe the facts and to help shift public behavior and attitude, influence policy and therefore contribute towards saving lives. The research is carried out by executing literature review, due to very less information and limited data. The result of the study highlighted the magnitude of people die each year as a result of road traffic crashes and shows the lack of road safety awareness of  public and road users.